Core-Shell UCNP@MOF Nanoplatforms for Dual Stimuli-Responsive Doxorubicin Release - Abuçafy, Marina P. [UNESP]; Ramin, Beatriz B. S. [UNESP]; Graminha, Angelica E. [UNESP]; Santos, Willy G. [UNESP]; Frem, Regina C. G. [UNESP]; Netto, Adelino V. G. [UNESP]; Pereira, José Clayston M. [UNESP]; Ribeiro, Sidney J. L. [UNESP] (American Chemical Society (ACS), 2025)
Nanocarrier systems with multifunctional capabilities hold great potential for targeted cancer therapy, particularly for breast cancer treatment. Metal-organic frameworks (MOFs) are notable for their high porosity and, in some cases, biocompatibility, with ZIF-8 being particularly advantageous due to its pH-sensitive degradability, enabling selective drug release in tumor environments. Additionally, lanthanide-doped upconversion nanoparticles (UCNPs) offer unique optical properties that enhance both imaging and therapeutic applications. In this study, NaYF4/Yb3+Er3+ UCNPs were synthesized via a hydrothermal method, subsequently coated with poly(acrylic acid) (PAA) and encapsulated within a ZIF-8 shell, forming of UCNP@ZIF-8 core-shell nanocomposites. This system was designed to leverage stimulation by a 980 nm laser and acidic pH to facilitate drug release. When exposed to this specific laser wavelength, the nanocomposites demonstrated significantly enhanced drug release, achieving up to 90% release of the incorporated antitumor drug, doxorubicin (DOX), in acidic environments. In vitro studies indicated selective cytotoxicity, with MCF-7 tumor cell viability decreasing from 85.7% to 20% following laser activation, while showing minimal toxicity toward healthy cells. These findings underscore the potential of the UCNP@ZIF-8 nanocarrier system as a pH and laser-responsive platform for improved cancer therapy, enabling precise control over drug delivery while minimizing side effects on surrounding healthy tissues.
Keywords: laser stimulation; metal−organic frameworks; multifunctional nanocarrier systems; pH-sensitive drug release; upconversion nanoparticles